Pola konsumsi media digital dan berita online Gen Z Indonesia (Jurnal Kajian Media, 2022)
Growing up amid the rapid development of information technology, Generation Z is faced with many choices of news and information sources. The internet and cell phones allow this generation to access news and information whenever and wherever they want. This study explores the consumption habits and tendencies of Generation Z Indonesia in accessing news and media using literature on media consumption, news consumption, and audience studies. Respondents are Gen Zers between the ages of 15 and 25, and they come from all throughout Indonesia. According to a poll of 1177 respondents (margin of error 3%), the majority of Indonesian Gen Z spends more than 8 hours a day accessing media, with social media serving as the primary source of news and information. The legitimacy of the media and the quality of news content are the most important factors for Generation Z when it comes to selecting the news they want to consume. Generation Z likewise likes extensive news information to quick but partial news items.